Validity and Reliability of an Ayurvedic Vikrti Scale for Assessment of Multiple Sclerosis - Sreedhar Palkuru; Suchitra S. Patil; Amit Singh; R. Nagarathna (Indian Journal of Ayurveda and Integrative Medicine KLEU)
Background: Ayurvedic interventions have proven to be effective in reducing symptoms of multiple sclerosis (MS). Objective: The present study has the primary objective to develop, validate the Ayurveda-based dosha-vikrti scale for assessment of patients with remitting MS (RRMS). Secondary objective was to evaluate the effect of Ayurveda intervention on vikrti status of the MS patients. Methodology: The Vikriti scale for the assessment of MS (MSVS) was developed based on 3 authentic texts of traditional Ayurveda texts and content validation was done by the Delphi method. Ten Ayurveda clinicians and one neurologist validated the scale items, and one psychologist reviewed the formatting of MSVS. Test–retest reliability of MSVS was assessed through a feasibility study that was conducted to look at the effect of add-on Ayuryoga in 60 patients of RRMS. Results: The final version of VSMS consists of 15 items, divided into three subscales: Vata (6 items), pitta (4), and kapha (4). Content validity was confirmed through the Delphi method. Cronbach’s alpha was above 0.8 for all 3 subscales of vata, pitta, and kapha. Reliability checked by correlation with the items on MS symptom scale (MSSS), a standard tool for the assessment of patients, showed a significant positive correlation (0.6–0.9). The feasibility study conducted on 60 participants with RRMS showed a significant reduction in scores on both MSVS and MSSS. Conclusion: The MSVS scale developed is a valid and reliable instrument for measuring vikrti in MS patients. The Ayuryoga intervention significantly reduces the dosha vikrti.